Socio-Scientific Issues in Chemistry Education for Improving 21st Century Skills: A Systematic Literature Review - Okmarisa, Heppy; Eka Sabila, Dwi; Maharani, Deswita; Sari, Nurmala (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This Systematic Literature Review (SLR) investigates the integration of Socio-Scientific Issues (SSI) in chemistry education to foster 21st-century skills. Using the PRISMA framework, 15 empirical studies published between 2020 and 2025 were analyzed from Google Scholar, SINTA, and Scopus. The findings indicate that SSI-based learning significantly impacts various student competencies, with the highest distribution of improvement observed in Critical Thinking (38%) and Science Literacy (31%), followed by Argumentation (13%). Additionally, Problem Solving, Creative Thinking, and Higher Order Thinking Skills (HOTS) each contributed 6% to the reported outcomes. The integration of real-world issues, such as green chemistry and polymer waste, proved effective in bridging abstract chemistry concepts with social-environmental responsibility. This study concludes that SSI serves as a vital catalyst for transforming chemistry pedagogy. Future research should focus on developing standardized assessment instruments to measure the long-term retention of these skills.